Synthesis, antitumour and antioxidant activities of novel α,β-unsaturated ketones and related heterocyclic analogues: EGFR inhibition and molecular modelling study - Walaa M. El-Husseiny; Magda A.-; Naglaa I. Abdel-Aziz; Adel S. El-Azab; Esam R. Ahmed; Alaa A.-M (Taylor & Francis Group, 2018)
New α,β-unsaturated ketones 4a,b; 5a-c; and 6a,b; as well as 4-H pyran 7; pyrazoline 8a,b; isoxazoline 9; pyridine 10-11; and quinoline-4-carboxylic acid 12a,b derivatives were synthesized and evaluated for in vitro antitumour activity against HepG2, MCF-7, HeLa, and PC-3 cancer cell lines. Antioxidant activity was investigated by the ability of these compounds to scavenge the 2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS•+). Compounds 6a, 6b, 7, and 8b exhibited potent antitumour activities against all tested cell lines with [IC50] ≅5.5-18.1 µΜ), in addition to significantly high ABTS•+ scavenging activities. In vitro EGFR kinase assay for 6a, 6b, 7, and 8b as the most potent antitumour compounds showed that; compounds 6b, and 7 exhibited worthy EGFR inhibition activity with IC50 values of 0.56 and 1.6 µM, respectively, while compounds 6a and 8b showed good inhibition activity with IC50 values of 4.66 and 2.16 µM, respectively, compared with sorafenib reference drug (IC50 = 1.28 µM). Molecular modelling studies for compounds 6b, 7, and 8b were conducted to exhibit the binding mode towards EGFR kinase, which showed similar interaction with erlotinib.